Germline determinants of the immune response in Asian breast cancer - Yap, Beverley Ling Shan (2025)
Breast cancer is a complex disease with heterogeneity in tumour characteristics and treatment response. Recently, Asian breast cancer patients were reported to have elevated immune scores in comparison to Caucasian breast cancer patients, however, germline genetic determinants associated with immune scores in Asian breast cancer patients remain undercharacterised. This study aims to identify the germline genetic variants associated with heritable immune scores in Asian breast tumours and determine the cellular pathways that drive immune scores within this population.